Navigating the online food environment: policy pathways for promoting food access, transparency, and healthy food choices online - Greenthal, Eva; Marx, Katherine; Friedman, Emily; John, Sara; Johnson, Joelle; LiPuma, Christina; Nara, DeAnna; Sorscher, Sarah; Gardner, Karen; Musicus, Aviva (Frontiers in Nutrition, 2024)
The internet is drastically changing how U.S. consumers shop for groceries, order food from restaurants, and interact with food marketing. There is an urgent need for new policies to help ensure that the internet is a force for good when it comes to food access, transparency, and nutrition. This article outlines actions that federal agencies—like the U.S. Department of Agriculture (USDA), U.S. Food and Drug Administration (FDA), and Federal Trade Commission (FTC)—and state and local governments can take to improve the online food environment. We recommend policies in three settings: online grocery retail, online restaurant ordering, and marketing on social media and other online platforms. For example, USDA could finalize regulations increasing access to online WIC and remove barriers to accessing online SNAP by requiring large retailers to waive online delivery and service fees for SNAP purchases. FDA could improve access to nutrition information by issuing guidance describing what product information should be available at the online point of selection. FTC could give better guidance on appropriate tactics when marketing to children and collect better data on how companies are marketing food to children online. Finally, state governments could pass laws like New York’s recently introduced Predatory Marketing Prevention Act to address false and misleading advertising of unhealthy foods aimed at children and other vulnerable groups.